Attitudes Regarding the Use of Hematopoietic Colony-Stimulating Factors and Maintenance of Relative Dose Intensity Among Gynecologic Oncologists. Issue 3 (1st March 2009) - Alvarez Secord, Angeles; Bae-Jump, Victoria; Havrilesky, Laura J.; Calingaert, Brian; Clarke-Pearson, Daniel L.; Soper, John T.; Gehrig, Paola A.
Abstract : Objective: To assess the attitudes regarding the use of colony-stimulating factor (CSF) and the maintenance of relative dose intensity (RDI) by gynecologic oncologists during the administration of chemotherapy to patients with epithelial ovarian cancer. Methods: A nationwide survey of 608 gynecologic oncologists was performed using a 19-point questionnaire. The questionnaire assessed the following domains: (1) demographic information, (2) patterns of CSF use during first-line and relapse chemotherapies for patients with epithelial ovarian cancer, and (3) use of CSFs to maintain RDI. Results: The response rate to the survey was 42% (n = 255). Eighty-six percent (220/255) of the respondents routinely administer chemotherapy. In the first-line setting, 67% of physicians who routinely administer chemotherapy preferred to use CSFs for secondary prophylaxis after a neutropenic complication, whereas only 2% would use CSFs for primary prophylaxis. In the recurrent disease setting, physicians were more likely to administer a regimen with minimal myelosuppression (74% reported "likely" or "very likely"), to dose delay or modify if neutropenic complications occur (78%), or to administer CSFs for secondary prophylaxis (85%) than to dose attenuate upon initiation of chemotherapy (49%) or to administer CSFs for primary prophylaxis (46%). Most physicians would administer CSFs to maintain RDI in both the first-line (75%) and palliative settings (62%), and 49% would strive to maintain a dose intensity of more than 85%. Conclusions: Most gynecologic oncologists use CSFs as secondary prophylaxis for neutropenic complications rather than as primary prophylaxis. Most gynecologic oncologists monitor RDI and use CSFs to maintain RDI in their patients with ovarian carcinoma.